Unexpected Effects of K + and Adenosine Triphosphate on the Thermal Stability of Na + ,K + -ATPase - Placenti, Maria Agueda (2017)
Na+,K+-ATPase is an integral membrane protein which couples ATP hydrolysis to the transport of three Na+ out and two K+ into the cell. The aim of this work is to characterize the effect of K+, ATP, and Mg2+ (essential activator) on the Na+,K+-ATPase thermal stability. Under all conditions tested, thermal inactivation of the enzyme is concomitant with a structural change involving the ATP binding site and membrane-associated regions. Both ligands exert a clear stabilizing effect due to both enthalpic and entropic contributions. Competition experiments between ATP and K+ showed that, when ATP is present, the inactivation rate coefficient exhibits a biphasic dependence on K+ concentration. At low [K+], destabilization of the enzyme is observed, while stabilization occurred at larger cation concentrations. This is not expected for a simple competition between the enzyme and two ligands that individually protect the enzyme. A model that includes enzyme species with none, one, or two K+ and/or one molecule of ATP bound explains the experimental data. We concluded that, despite both ligands stabilizing the enzyme, the species with one K+ and one ATP simultaneously bound is unstable.